SEASONALITY AND BIOCONTROL OF MAIESTAS KNIGHTI (HEMIPTERA: CICADELLIDAE) ON SOME VEGETABLE PLANTS OF CUCURBITACEAE IN ERBIL PROVINCE, KURDISTAN REGION -IRAQ - H. Q. Hammamurad; Z. Z. Omar; N. A. Mawlood (مجلة الأنبار للعلوم الزراعية)
Maiestas knighti belongs to the family Cicadellidae order Hemiptera. It is a severe insect that infects plants of the Cucurbitaceae family. The work was conducted to study the insect ecology and its management. Experiments were conducted, and population numbers were deemed in the field during spring and autumn on snake-cucumber and melon crops. Various yellow and blue sticky traps were used to catch and monitor the pests. Bacillus thuriengiensis and Beauveria bassiana were used as bio-pesticides, and the extracts of Tagetes erecta were applied with recommended concentrations to manage the insect. The bio-pesticides rates were involved (2g/L B. thuriengiensis, 5g/L B. bassiana, and 10 ml/L T. erecta) to be used in fields, then reduction was recorded on the 3rd, the 5th, and 7th days. The maximum population was observed on the vegetables and with yellow sticks in the fall season. The highest decrease was recorded with B. bassiana on snake cucumber and by the plant extract on melon vegetables.